PENGEMBANGAN MODUL PEMBELAJARAN PADA MATA PELAJARAN PEKERJAAN DASAR ELEKTROMEKANIK KELAS X TITL SMK MUHAMMADIYAH 1 PADANG - Nofri D Nofri; Oriza Candra (JTEV (Jurnal Teknik Elektro dan Vokasional), 2019)
The purpose of this study is to produce a Learning Module that is valid, practical, and effective. This type of research is research and development. This study uses a 4-D model research procedure which consists of empar stages namely defining, designing, developing and disseminating. The subject of this study was the tenth grade students of Muhammadiyah 1 SMK Padang. The validation test consists of 3 validators, practicality tests carried out by 2 subject teachers and 30 students of the XTITL class of the Muhammadiyah 1 Padang Vocational High School as respondents to the development of the learning module. Data effectiveness is obtained from the assessment of student learning outcomes using post test. Based on the results of the research that has been done, it can be concluded that the development of this module was declared successful in producing media that are valid, practical, and effective. Validity test results from 3 validators were declared valid with an average of 90.66% categorized as very valid. The practical test results by subject teachers with an average of 94.76% are very practical, while the practicality test results by students an average of 93.08% are categorized as very practical. Effectiveness test results obtained classical completeness of 86.66%. Thus the learning module as a learning medium is effectively used in the learning process at school.